Effects of Autogenic Training on Stress Response and Heart Rate Variability in Nursing Students - Seung-Joo Lim, PhD, RN; Chunmi Kim, PhD, RN (Elsevier, 2014)
Purpose: This study was undertaken to confirm the effects of autogenic training (AT) on stress response and heart rate variability in nursing school students experiencing stress related to clinical training. Methods: The study was carried out from September 2012 to April 2013 in a quasi-experimental nonequivalent control group using a pretest-posttest design. The participants were 40 nursing students in their third year at either of two nursing colleges. All consented to participate. Nineteen nursing students at one college were assigned to the experimental group and underwent the 8-week AT program, and the other 21 were assigned to the control group and did not undergo any training. Stress response was assessed by questionnaire and HRV was measured three times, that is, before the program, at the end of the program, and 6 months after the end of the AT program. Results: A significant time/group interaction was found for stress response (F = 4.68, p = .012), a subjective indicator. However, no significant interaction was found for the objective indicators of heart rate variability, normalized low frequency (F = 2.59, p = .090), normalized high frequency (F = 2.59, p = .090), or low frequency to high frequency ratio (F = 1.38, p = .257). Conclusion: The results suggest that AT provides an acceptable approach to stress reduction in nursing students.